Soil profile at vibratory compaction area in Kerteh, Terengganu / Mohd Firdaus Mohd Wahid - Mohd Wahid, Mohd Firdaus (2005)
Vibro-compaction is a recognized and an accepted technique for stabilization of loose or granular soil conditions. This method has been used to improve bearing capacity and works best in loose sands consist of 12% fine or below, (Schaefer, 1997). This study will explore the applicability of this technique based on fine content and soil grading. Thus, sampling was conducted using wet borehole method in Kertih along the known Vibro-compaction improvement area. The borehole was driven at 14 different locations. For each borehole, minimum 1 Kg sample was collected at every 0.5 m until 4.0 m depth as minimum. With regard to BS 1377, laboratory testing such as moisture content, wet sieve and dry sieve was conducted to determine the moisture content as well as total fine content for every sample collected and this laboratory testing took place at UiTM Pulau Pinang Laboratory. From the laboratory test result, it was found that the maximum fine content is 12%. This matched the maximum fine content as suggested by Schafer, 1997. Then, the fine content pattern along the study area was illustrated to perform the best view of fine content along the study area. From this study, it brings the confidence that the use of Vibro-compaction at the study area suit the fine content as suggested by expert.